2019
DOI: 10.1029/2019jd031432
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Terrestrial Water Storage Declining Trends in the Yellow River Basin

Abstract: Under dual impacts from climate change and human activities, the Yellow River Basin (YRB) of China suffers from droughts and water scarcity. Understanding variations of terrestrial water storage (TWS) over the YRB is significant and beneficial to regional water resources management and sustainable development. This study investigates TWS variations in the YRB using data sets from two solutions (RL05 and RL06) of the Gravity Recovery and Climate Experiment (GRACE) satellites, as well as from global land surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 99 publications
(120 reference statements)
0
22
0
Order By: Relevance
“…The black dash lines mark the rough boundaries of three topographic regions: upper (altitudes greater than 2000 m), middle (between 1000 and 2000 m), and lower (less than 1000 m) reaches. SR denotes the source region of the YR significantly since 1986 (Cong et al 2010) and terrestrial water storage in the YRB has therefore dramatically declined over recent years (Jing et al 2019). Water scarcity, driven by growing demand and persistent droughts, has more serious implications for water and food security than was recognized until recently (Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The black dash lines mark the rough boundaries of three topographic regions: upper (altitudes greater than 2000 m), middle (between 1000 and 2000 m), and lower (less than 1000 m) reaches. SR denotes the source region of the YR significantly since 1986 (Cong et al 2010) and terrestrial water storage in the YRB has therefore dramatically declined over recent years (Jing et al 2019). Water scarcity, driven by growing demand and persistent droughts, has more serious implications for water and food security than was recognized until recently (Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these techniques, a range of machine-learning techniques have been applied to the problem, including MLP in [12,[19][20][21][22][23], SVR in [19,24] and recently RFs in [25,26]. The use of XGB is rare in the scheme of groundwater prediction, and is found in only a few studies such as [27,28].…”
Section: Background On Groundwater Predictionmentioning
confidence: 99%
“…Previous studies have evaluated the changes in TWS based on GRACE data, reaching a consistent conclusion that the TWS decreased in the past ten years, with significant spatial variations across the YRB [26][27][28]. Therefore, studies on the impact of climate change and human activities on TWS variations have gained more attention [29][30][31]. Many studies have shown that the rise in temperature and precipitation, the melting of glaciers, and the degradation of permafrost led to increased TWS in the source area of the YRB [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the rise in temperature and precipitation, the melting of glaciers, and the degradation of permafrost led to increased TWS in the source area of the YRB [32][33][34]. For the middle reaches of the YRB, the essential area of the Loess Plateau with a large population density, vegetation restoration, mining, and human water use were the major factors for the decreased TWS [29,31,35,36]. Additionally, some studies have also indicated that reservoir operation caused a significant change in the TWS in the YRB [30,37].…”
Section: Introductionmentioning
confidence: 99%